Electrode for secondary battery, method for manufacturing same, and secondary battery including same
By controlling the drying rate of the lithium secondary battery electrode paste at the center and edges to make it similar, and using a specific coating method, the problems of raised, cracks or wrinkles of the electrode edges are solved, and the life characteristics and productivity of the battery are improved.
Patent Information
- Application Number
- CN202380057335.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-05
- Filing Date
- 2023-07-24
- Publication Date
- 2025-03-14
AI Technical Summary
When manufacturing the electrode of a lithium secondary battery, the edges of the electrodes are raised, cracked or wrinkled due to the drying process, which affects the life characteristics of the battery.
By controlling the drying rate of the electrode slurry at the center and edges to make it similar, the slit die head or double slit die head is used for coating to ensure that the solid content of the edge is lower than that of the center, thereby reducing the difference in drying rate.
It effectively solves the problems of raised, cracks or wrinkles on the edge of the electrode, improves the surface quality of the electrode, and improves the life characteristics and productivity of the battery.
Smart Images

Figure CN119631189A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an electrode for a secondary battery, a method for manufacturing the electrode, and a secondary battery including the electrode. Background Art
[0002] In recent years, with the emergence of global warming issues, the demand for environmental protection technologies to cope with the problem has also increased rapidly. In particular, with the increase in demand for technologies related to electric vehicles and energy storage systems (ESS), the demand for lithium secondary batteries, which have attracted much attention as energy storage devices, has also exploded. Therefore, research is being conducted to improve the life characteristics of lithium secondary batteries.
[0003] Typically, electrodes for lithium secondary batteries are manufactured by the following method: an electrode active material, a conductive material, and a binder are mixed and dispersed in a solvent to prepare an electrode slurry, and the electrode slurry is coated on a current collector and then dried to manufacture electrodes for lithium secondary batteries. When the coated electrode slurry is dried, the edge portion is dried preferentially based on the width direction, so the drying rates of the center portion and the edge portion of the coated electrode slurry based on the width direction differ. As a result, after the electrode slurry is dried, surface quality problems may occur, such as the edge portion of the electrode warping or cracks (crack) or wrinkles (wrinkle) formed on the surface of the electrode edge portion. In addition, when electrodes with surface quality problems are assembled into batteries, lithium salts may precipitate due to cracks or wrinkles generated on the surface of the electrode, so the life characteristics of the battery may deteriorate.
[0004] Therefore, there is a need to develop an electrode for a secondary battery that improves the above-mentioned problems occurring due to a drying process in the process of manufacturing the electrode.
[0005] [Prior art literature]
[0006] [Patent Document]
[0007] (Patent Document 1) Korean Patent Publication No. 10-2017-0100377 (Publication Date: September 4, 2017) Summary of the invention
[0008] 1. Technical issues to be resolved
[0009] According to one aspect of the present invention, an electrode for a secondary battery, a method for manufacturing the electrode, and a secondary battery including the electrode can be provided, wherein the electrode can solve the problem of warping of the edge of the electrode or formation of cracks or wrinkles on the surface of the edge of the electrode due to a drying process during the manufacturing of the electrode.
[0010] According to another aspect of the present invention, there can be provided an electrode for a secondary battery and a method for manufacturing the electrode, which can improve the surface quality of the electrode by solving the above-mentioned problems and can improve the life characteristics of the battery while improving productivity.
[0011] The secondary battery electrode of the present invention can be widely used in electric vehicles, battery charging stations, other green technology fields such as solar power generation and wind power generation using batteries. In addition, the secondary battery electrode of the present invention can be used in eco-friendly electric vehicles and hybrid vehicles that prevent climate change by suppressing air pollution and greenhouse gas emissions.
[0012] (II) Technical solution
[0013] As a solution to achieve the above technical problem, this specific embodiment provides an electrode for a secondary battery, the electrode for a secondary battery comprising: a current collector; and an electrode active material layer, the electrode active material layer is located on at least one side of the current collector, and the electrode for a secondary battery satisfies the following relationship 1.
[0014] [Equation 1]
[0015] Sa≤10.0
[0016] In the above relational expression 1, Sa is the average surface roughness value (μm) of the edge portion of the electrode active material layer based on the width direction.
[0017] In a specific embodiment, the electrode active material layer has an edge portion with a width direction as a reference, and a unit area of 10 cm 2 The number of cracks can be less than 5.
[0018] In a specific embodiment, the maximum long diameter of the cracks at the edge of the electrode active material layer based on the width direction may be less than 100 mm.
[0019] In addition, as another solution to achieve the above technical problem, this specific embodiment provides a method for manufacturing an electrode for a secondary battery, the manufacturing method comprising the following processes: a) coating an electrode slurry on at least one side of a current collector; and b) drying the coated electrode slurry and satisfying the following relationship 2.
[0020] [Equation 2]
[0021] We / Wc<1
[0022] In the above relational expression 2, based on the width direction of the applied electrode slurry, Wc is the solid content of the electrode slurry applied at the center, and We is the solid content of the electrode slurry applied at the edge.
[0023] In a specific embodiment, the value of We / Wc in the relational expression 2 may be greater than or equal to 0.8 and less than 1.
[0024] In a specific embodiment, the process a) may include the following processes: a1) preparing a first electrode slurry having a first solid content and a second electrode slurry having a second solid content lower than the first solid content; and a2) on at least one side of the current collector, based on the width direction, applying the first electrode slurry to the center portion and applying the second electrode slurry to the edge portion.
[0025] In a specific embodiment, the process a2) can be carried out by the following process: on at least one side of the current collector, based on the width direction, use a slit die to apply the first electrode slurry to the center portion, and use a micro slit die to apply the second electrode slurry to the edge portion; or on at least one side of the current collector, use a double slit die coater, based on the width direction, apply the second electrode slurry to the edge portion, and apply the first electrode slurry to the center portion.
[0026] In a specific embodiment, based on the total width of the coated electrode slurry, the width of the edge portion may be 15% or less.
[0027] In a specific embodiment, the electrode slurry coated on the central portion and the edge portion may have the same composition.
[0028] In a specific embodiment, the viscosity Vc of the electrode slurry coated on the central portion may be 1000-10000 cP.
[0029] In a specific embodiment, the viscosity Ve of the electrode slurry coated on the edge portion may be 1000-6000 cP.
[0030] In a specific embodiment, the electrode slurry coated on the central portion and the edge portion may be coated with the same thickness.
[0031] In addition, as another solution to achieve the above technical problem, the present embodiment provides a secondary battery, which includes: the electrode according to the above embodiment; a separator; and an electrolyte.
[0032] (III) Beneficial effects
[0033] The present invention can solve the problems of warping, cracking or wrinkling of the edge of the electrode surface during drying by controlling the drying rates of the center and edge parts based on the width direction of the electrode to be similar, thereby improving the surface quality of the electrode and improving productivity.
[0034] Furthermore, the present invention can improve the life characteristics of a battery including the electrode by solving the above-mentioned problems occurring in the edge portion. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 is a diagram showing an electrode slurry coated on a current collector according to one specific embodiment.
[0036] Figure 2 is the Figure 1 A-A' section.
[0037] Figure 3 and Figure 4 This is a diagram for explaining surface quality problems such as warping, cracking, or wrinkling at the edge of an electrode that occur when the drying rates of the center and edge are different based on the width direction of the electrode. Figure 3 is a diagram showing an electrode before the electrode slurry applied on a current collector is dried. Figure 4 is a diagram showing an electrode after the electrode slurry coated on the current collector is dried.
[0038] Figure 5 This is a diagram for confirming whether cracks have occurred in the edge portion of the electrode of Example 1.
[0039] Figure 6 This is a diagram for confirming whether cracks have occurred in the edge portion of the electrode of Example 2.
[0040] Figure 7 This is a diagram for confirming whether cracks have occurred in the edge portion of the electrode of Comparative Example 1. Best Mode for Carrying Out the Invention
[0041] By referring to the drawings and the specific embodiments described in detail, the advantages and features of the present invention and the methods for achieving them can be clearly understood. However, the present invention is not limited to the specific embodiments disclosed below, but can be implemented by various schemes that are different from each other, and this specific embodiment is provided to fully disclose the present invention and fully explain the scope of the invention to those skilled in the art to which the present invention belongs. The present invention is only defined by the scope of the claims.
[0042] Unless otherwise defined, all terms (including technical terms and scientific terms) used in this specification can be used with the meanings that can be generally understood by technicians in the technical field to which the present invention belongs. Throughout the specification, unless otherwise specifically stated to the contrary, when a part is described as "including" or "comprising" a certain constituent element, it means that other constituent elements can also be included, rather than excluding other constituent elements. In addition, unless otherwise specifically stated in the text, the singular form also includes the plural form.
[0043] In this specification, when a layer, film, region, plate or the like is described as being “on” or “over” another part, this includes not only the case of being “directly” “on” another part but also the case of having other parts in between.
[0044] Below, refer to Figure 1 and Figure 2 , the present invention is described in detail. However, this is only exemplary, and the present invention is not limited to the specific embodiments described exemplarily.
[0045] Figure 1 and Figure 2 is a diagram showing an electrode according to a specific embodiment. Figure 1 In the figure, the area marked with a dotted line may be a portion that becomes an electrode when the battery is assembled later. The area marked with a dotted line in the coated portion 10 may be a portion that forms a current collector-electrode active material layer later, and the area marked with a dotted line in the uncoated portion 20 may be a portion that forms an electrode tab later by a cutting process or the like.
[0046] In this specification, unless otherwise specified, the "length direction" refers to Figure 1 The “width direction” refers to the direction (y-axis direction) parallel to the coating running direction of the electrode during the manufacturing process of the electrode. Figure 1 The direction perpendicular to the coating advancing direction (x-axis direction) is shown.
[0047] In this specification, the "edge (side) part" of an electrode may refer to Figure 1 and Figure 2 The edge region 12 shown in FIG. 1 is an end part of the electrode coating portion 10 on the electrode non-coated portion 20 side of the electrode 1 in the width direction. In this specification, the “center portion” may refer to the end part of the electrode non-coated portion 20 on the electrode coating portion 10 in the width direction. Figure 1 and Figure 2 The central region 11 shown in the figure refers to the region of the electrode coating portion 10 excluding the edge portion 12 based on the width direction.
[0048] In this specification, when one electrode slurry is uniformly coated on one side of the current collector, the width of the edge portion 12 may refer to an interval of less than 15% based on the total width of the electrode coating portion 10. When two different electrode slurries are coated on the center and edge portions, respectively, the width of the edge portion 12 may refer to an interval where an electrode slurry different from the electrode slurry coated on the center portion is coated on the edge portion. In a specific embodiment, the width of the edge portion 12 may be 1-20 mm, or in a specific embodiment, the width of the edge portion 12 may be 5-20 mm, but is not limited thereto.
[0049] Reference Figure 3 and Figure 4 In the conventional secondary battery electrode, when the coated electrode slurry is dried, in the case of the edge portion adjacent to the uncoated portion, the heat conduction of the current collector may act as an additional heat source, thereby accelerating the drying, and thus the drying rate of the center portion and the edge portion based on the width direction may differ. Due to the difference in the drying rate, Figure 4 As shown, after drying, the edge of the electrode may be lifted or cracks or wrinkles may be formed on the surface of the edge of the electrode.
[0050] According to a specific embodiment of the present invention that solves this problem, an electrode for a secondary battery can be provided, which includes: a current collector; and an electrode active material layer, wherein the electrode active material layer is located on at least one side of the current collector, and the electrode for a secondary battery satisfies the following relationship 1.
[0051] [Equation 1]
[0052] Sa≤10.0
[0053] In the above relational expression 1, Sa is the average surface roughness value (μm) of the edge portion of the electrode active material layer based on the width direction.
[0054] In a specific embodiment, the average surface roughness Sa can be the average value of the surface roughness values measured at any five points on the edge portion based on the width direction of the electrode active material layer with an observation area of 20 mm in width × 20 mm in length using a surface roughness measuring tool in a confocal microscope, but is not limited thereto.
[0055] In a specific embodiment, the average surface roughness Sa value can be 10.0 μm or less, 8.0 μm or less, 6.0 μm or less, 5.0 μm or less, more than 0 μm, 1.0 μm or more, 1.5 μm or more, or a value between the above values. The lower the average surface roughness Sa value, the better the surface quality and life characteristics of the electrode, so there is no particular limitation, but in a specific embodiment, the average surface roughness Sa value can be more than 0 μm and less than 10.0 μm, more than 0 μm and less than 8.0 μm, more than 0 μm and less than 6.0 μm, more than 0 μm and less than 5.0 μm, or more than 1.0 μm and less than 5.0 μm.
[0056] In the electrode satisfying Relationship 1 of the specific embodiment, after the electrode slurry is dried, problems such as the edge of the electrode active material layer not warping or cracks or wrinkles forming on the edge surface of the electrode active material layer will not occur, so it can have improved surface quality and enhanced life characteristics.
[0057] In a specific embodiment, the electrode active material layer has an edge portion with a width direction as a reference, and a unit area of 10 cm 2 The number of cracks may be less than 5. In a specific embodiment, the number of cracks may be 3, 2, 1 or 0. The unit area 10cm 2 It is the area formed by the width a and the length b of the edge portion, which can be calculated as the product of a and b, and the length b can be determined according to the width a of the edge portion. For example, when the width a of the edge portion is 20 mm, the length b can be 50 mm.
[0058] In a specific embodiment in which the number of cracks is at least 1, the maximum long diameter of the cracks at the edge of the electrode active material layer based on the width direction may be less than 100 mm. Wherein, the "long diameter" of the crack refers to the length of the longest major axis direction on the crack, and the "maximum long diameter" refers to the largest long diameter value among the long diameter values of the crack. In a specific embodiment for further improving the surface quality of the electrode and further improving the life characteristics, the maximum long diameter of the crack may be less than 80 mm, less than 50 mm, less than 30 mm, less than 10 mm or less than 5 mm. At this time, the lower limit of the maximum long diameter of the crack may be 0.1 mm or 1 mm, but is not limited thereto.
[0059] In the electrode according to the specific embodiment, by improving the problems of warping, cracking, or wrinkling of the edge portion of the electrode active material layer occurring when manufacturing the electrode, the electrode has excellent surface quality and has the effect of significantly improving life characteristics.
[0060] The method for manufacturing the electrode as a scheme for providing the electrode having excellent surface quality and life characteristics according to the specific embodiment is not particularly limited, but as a scheme for providing the electrode according to the specific embodiment, the manufacturing method of the following specific embodiment can be used.
[0061] like Figure 3 and Figure 4 As shown, in the conventional secondary battery electrode, when the coated electrode slurry is dried, in the case of the edge portion adjacent to the uncoated portion, the heat conduction of the current collector may serve as an additional heat source, thereby accelerating the drying, and thus the drying rate of the center portion and the edge portion based on the width direction of the electrode may differ. Figure 4 As shown, after drying, the edge of the electrode may be lifted or cracks or wrinkles may be formed on the surface of the edge of the electrode.
[0062] A specific embodiment of the present invention to solve this problem can provide a method for manufacturing an electrode for a secondary battery, the manufacturing method comprising the following processes: a) coating an electrode slurry on at least one side of a current collector; and b) drying the coated electrode slurry, and satisfying the following Relationship 2.
[0063] [Equation 2]
[0064] We / Wc<1
[0065] In the above relational expression 2, based on the width direction of the applied electrode slurry, Wc is the solid content (weight %) of the electrode slurry applied at the center, and We is the solid content (weight %) of the electrode slurry applied at the edge.
[0066] According to the one specific embodiment, when the above We / Wc value range is satisfied, a region with a high solid content can be formed in the center, and a region with a low solid content can be formed in the edge, based on the width direction, so the difference in the drying rate of the electrode slurry applied to the center and the edge can be reduced. Therefore, the present invention solves the problem of warping of the electrode edge or formation of cracks or wrinkles on the surface of the electrode edge due to the difference in the drying rate, thereby providing a secondary battery electrode with significantly improved surface quality.
[0067] In a specific embodiment, considering that the drying rate of the edge portion is higher than that of the center portion, in order to reduce the difference in drying rate of the electrode slurry coated on the edge portion and the center portion, the value of We / Wc in the relationship 2 can be greater than 0.8, greater than 0.85, less than 1, less than 0.99, less than 0.98, less than 0.95, or a value between the above values.
[0068] The lower limit is not particularly limited, but by controlling the value of We / Wc to be above an appropriate level, the difference in the drying rate of the electrode slurry applied to the edge and the center can be further reduced, thereby further improving the surface quality, productivity and life characteristics of the electrode. Considering the above effects, in a more specific embodiment, the value of We / Wc in the relational expression 2 can be 0.8 or more and less than 1 or 0.85 or more and less than 1.
[0069] In a more specific embodiment, in order to further improve the surface quality, productivity and life characteristics of the electrode by further reducing the difference in the drying rate of the electrode slurry coated on the edge portion and the center portion within a wider range of the width of the edge portion and a narrower range of the width of the edge portion, the value of We / Wc in the relationship 2 can be greater than 0.8 and less than 0.95 or greater than 0.85 and less than 0.95.
[0070] The scheme for realizing the relational expression 2 of the specific embodiment is not particularly limited, and all methods known in the technical field can be used in various ways.
[0071] In a specific embodiment, the process a) may include the following processes: a1) preparing electrode slurry; and a2) coating the prepared electrode slurry on at least one side of a current collector. Specific embodiments of each process are described below.
[0072] In a specific embodiment, the process a1) may be a process for preparing an electrode slurry comprising an electrode active material, a binder, a conductive material and a solvent. In a specific embodiment, the solid content in the electrode slurry may be 40% by weight or more based on the total weight of the electrode slurry. In a specific embodiment, the solid content in the electrode slurry may be 40-65% by weight or 40-60% by weight.
[0073] In a specific embodiment, the electrode active material can be used without restriction as long as it is an electrode active material commonly used in secondary batteries. Non-limiting examples of negative electrode active materials include any one or more of carbon-based negative electrode active materials, silicon-based negative electrode active materials, and mixtures thereof. Non-limiting examples of carbon-based negative electrode active materials may be any one or more selected from artificial graphite, natural graphite, and hard carbon. Non-limiting examples of silicon-based negative electrode active materials may be selected from Si, SiO xAny one or more of (0 < x < 2), Si-Q alloy (where Q is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, Group 15 elements, Group 16 elements, transition metals, rare earth elements, and combinations thereof, and is not Si), and Si-carbon composite. Non-limiting examples of the positive electrode active material can be composite oxides of any one or more of cobalt, manganese, and nickel with lithium. Without departing from the scope of the present invention, the electrode active material can be replaced by other components.
[0074] In a specific embodiment, the binder can be used without limitation as long as it can make the electrode active material particles adhere well to each other and at the same time make the electrode active material adhere well to the current collector. As non-limiting examples of the binder, water-soluble binders can be cited. Specifically, styrene-butadiene rubber (SBR), acrylated styrene-butadiene rubber, polyvinyl alcohol, sodium polyacrylate, copolymers of propylene and olefins having 2 to 8 carbon atoms, copolymers of (meth)acrylic acid and (meth)acrylic acid alkyl esters, or combinations thereof can be cited. Without departing from the scope of the present invention, the binder can be replaced by other components.
[0075] In a specific embodiment, when using the water-soluble binder, the water-soluble binder can make the electrode active material adhere well to the current collector without affecting the viscosity of the slurry, so it is preferred. However, since the electrode active material and the conductive material are fine particles, the slurry may easily gel, so a thickener can be further included. The thickener is used to impart viscosity to the slurry to prepare a stable slurry. As non-limiting examples, cellulose-based compounds can be used as the thickener. Specifically, one or more mixtures of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, or their alkali metal salts, etc. can be used. The alkali metal can be Na, K, or Li. Without departing from the scope of the present invention, the thickener can be replaced by other components.
[0076] In a specific embodiment, the solvent can be used without restriction as long as it is a solvent commonly used in electrode slurries. As a non-limiting example, the solvent for the negative electrode can be a single solvent of any of the following solvents or a mixed solvent containing two or more of the following solvents: water, pure water, deionized water, distilled water, ethanol, isopropanol, methanol, acetone, n-propanol and tert-butanol. As a non-limiting example, the solvent for the positive electrode can be a single solvent selected from any of the following solvents or a mixed solvent containing two or more selected from the following solvents: amine solvents such as N, N-dimethylaminopropylamine and diethyltriamine; ether solvents such as ethylene oxide and tetrahydrofuran; ketone solvents such as methyl ethyl ketone; ester solvents such as methyl acetate; and non-protonic polar solvents such as dimethylacetamide and N-methyl-2-pyrrolidone. Without departing from the scope of the present invention, the solvent may be replaced by other constituent elements.
[0077] In a specific embodiment, the conductive material is used to impart conductivity to the electrode, and the conductive material is not particularly limited as long as it is an electronic conductive material that does not cause chemical changes in the battery. As a non-limiting example, the conductive material may include any one or more of natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber and carbon nanotubes. Without departing from the scope of the present invention, the conductive material may be replaced by other constituent elements.
[0078] In a specific embodiment, after the process a1), a process a2) of coating the prepared electrode slurry on at least one side of a current collector may be performed.
[0079] In a specific embodiment, the current collector may use any one of copper foil, nickel foil, stainless steel foil, titanium foil, foam nickel, foam copper, and a polymer substrate coated with a conductive metal, but is not limited thereto.
[0080] The coating can use any known coating method that is commonly used for coating liquid phase to form film. According to non-limiting examples, the coating can use any method or a combination of two or more methods in spraying, dip coating, spin coating, gravure coating, slot extrusion coating, blade coating, roller coating, inkjet printing, flexographic printing, screen printing, electrohydrodynamic printing, microcontact printing, embossing, reverse offset printing, rod coating and gravure offset printing.
[0081] In a specific embodiment, the viscosity Vc of the electrode slurry coated on the center portion can be above 1000cP, above 1500cP, above 2000cP, above 2500cP, above 3000cP, below 10000cP, below 9000cP, below 8000cP, below 7000cP, below 6000cP, below 5000cP or a value between the above values. In a specific embodiment, the Vc can be 1000-10000cP, 2000-8000cP or 3000-6000cP.
[0082] In a specific embodiment, the viscosity Ve of the electrode slurry coated on the edge portion can be above 1000cP, above 1500cP, below 6000cP, below 5000cP, below 4500cP, below 4000cP, below 3500cP or a value between the above values. In a specific embodiment, the Ve can be 1000-6000cP, 1500-5000cP or 1500-4500cP.
[0083] The viscosity Vc and Ve of the electrode slurry refer to the viscosity when the electrode slurry is coated on the current collector, and are measured at room temperature and pressure using a Brookfield rotational viscometer in 1s -1 The shear rate is measured with a tolerance of ±100cP.
[0084] As shown in the specific embodiment, when the electrode slurry satisfying the above viscosity range is applied to the center and edge portions, the ease of the slurry coating operation can be improved and an electrode active material layer with a uniform thickness can be formed.
[0085] In one specific embodiment, the electrode slurry applied to the center and the edge can be applied with the same thickness. As shown in the specific embodiment, when the electrode slurry is applied to the center and the edge with the same thickness, an electrode active material layer with uniform thickness can be formed even after the electrode slurry is dried, and the electrode active material layer can have a uniform composition.
[0086] Although not particularly limited, as a non-limiting example of a solution for better realizing the relationship 2, a method according to the following specific embodiment may be selectively used. In a specific embodiment, process a) may include the following process: a1) preparing a first electrode slurry having a first solid content and a second electrode slurry having a second solid content lower than the first solid content; and a2) on at least one side of the current collector, based on the width direction, applying the first electrode slurry to the center portion and applying the second electrode slurry to the edge portion.
[0087] By carrying out the process a1) and the process a2) of the specific embodiment, the range of the We / Wc value can be better achieved, so the difference in the drying rate of the electrode slurry applied to the center and the edge can be further reduced. As a result, the problem of warping, cracks or wrinkles on the edge of the electrode surface during drying can be solved, thereby further improving the surface quality of the electrode, further improving productivity, and further improving life characteristics.
[0088] In one specific embodiment, the first electrode slurry and the second electrode slurry may have the same solid content (electrode active material, binder and conductive material) composition, while the solid content (weight %) of the slurry excluding the solvent may be different from each other.
[0089] In addition, in the one specific embodiment, the first electrode slurry and the second electrode slurry can be coated on the current collector simultaneously or sequentially, and the coating order is not particularly limited. The coating method is not particularly limited, but the following coating methods can be selectively used.
[0090] As a first embodiment, in the process a2), the first electrode slurry can be applied to the center of at least one side of the current collector using a slot die, and the second electrode slurry can be applied to the edge using a micro slot die, based on the width direction. The first electrode slurry and the second electrode slurry can be applied simultaneously or sequentially, without particular limitation.
[0091] As a second embodiment, in process a2), a double-slit die coater including a lower slit and an upper slit can be used on at least one side of the current collector, and the discharge port facing the center portion is blocked with a shim based on the width direction, and the second electrode slurry is applied to the edge portion, and the discharge port facing the edge portion is blocked with a shim based on the width direction, and the first electrode slurry is applied to the center portion. The first electrode slurry and the second electrode slurry can be applied simultaneously or sequentially, without particular limitation. The first electrode slurry can be applied through the lower slit or the upper slit, and the second electrode slurry can be applied through the remaining slits, without particular limitation.
[0092] In the first and second embodiments, when two electrode slurries with different solid contents are separately coated using a slit die in the center portion and a micro slit die in the edge portion as shown in the first embodiment, the solid content can be more accurately controlled, thereby being beneficial in ensuring the desired surface quality, productivity and life characteristics of the electrode.
[0093] In a specific embodiment, after the above process a), a process b) of drying the coated electrode slurry may be performed.
[0094] Although there is no particular limitation, in a specific embodiment, the drying temperature can be above 60°C, above 80°C, above 100°C, below 150°C, below 140°C, below 130°C, or a value between the above values. In a specific embodiment, the drying temperature can be 60-150°C, 80-140°C, or 100-130°C.
[0095] Although not particularly limited, in a specific embodiment, the drying time can be more than 0 seconds, more than 30 seconds, more than 40 seconds, more than 1 minute, less than 5 minutes, less than 4 minutes, less than 3 minutes, less than 2 minutes, or a value between the above values. In a specific embodiment, the drying time can be more than 0 seconds and less than 5 minutes, more than 30 seconds and less than 4 minutes, or more than 40 seconds and less than 3 minutes.
[0096] According to a specific embodiment, after the electrode slurry is dried, it can be rolled to an appropriate density to manufacture an electrode having an electrode active material layer formed on at least one side of the current collector. At this time, the rolling conditions such as the compaction density can be applied without restriction to all known electrode rolling methods, and there is no particular limitation.
[0097] In addition, the present invention provides a secondary battery, the secondary battery comprising the electrode, separator and electrolyte of the specific embodiment. In a specific embodiment, the electrode can be a positive electrode or a negative electrode according to the type of electrode active material contained in the electrode active material layer, and the same description as the above description can be applied, so for convenience, the detailed description is omitted.
[0098] In a specific embodiment, the diaphragm can use all diaphragms known in the art, without particular limitation. As non-limiting examples of the diaphragm substrate, a porous substrate formed of glass fiber, polyester, polyethylene, polypropylene, polytetrafluoroethylene or a combination thereof can be cited, and can be in the form of a non-woven fabric or a woven fabric, and can be selectively used in a single-layer structure or a multilayer structure. In addition, in a specific embodiment, for the purpose of improving heat resistance, the diaphragm can use a diaphragm having an inorganic particle layer formed on the diaphragm substrate.
[0099] In a specific embodiment, the electrolyte may include a non-aqueous organic solvent and an electrolyte salt. As non-limiting examples of the non-aqueous organic solvent, ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), 1,2-dimethoxyethane (DME), γ-butyrolactone (BL), tetrahydrofuran (THF), 1,3-dioxolane (DOL), diethyl ether (DEE), methyl formate (MF), methyl propionate (MP), sulfolane (S), dimethyl sulfoxide (DMSO), acetonitrile (AN) or a mixture thereof may be cited. As non-limiting examples of the electrolyte salt, when the electrolyte metal is lithium, the electrolyte salt may be LiPF6, LiBF4, LiTFSI, LiSbF6, LiAsF6, LiClO4, LiCF3SO3, Li(CF3SO2)2N, LiC4F9SO3, LiSbF6, LiAlO4, LiAlCl4, LiN(C x F 2x+1 SO2)(C y F 2y+ 1SO2) (wherein x and y are natural numbers), LiCl, LiI or a mixture thereof. The organic solvent and the electrolyte salt may be replaced by other constituent elements without departing from the scope of the present invention.
[0100] Furthermore, in a specific embodiment, the electrolyte may further contain a known solvent or additive to improve charge and discharge characteristics, flame retardancy, etc., as required.
[0101] In a method for manufacturing a secondary battery according to a specific embodiment, the manufactured electrode and separator can be stacked to form an electrode assembly, and the manufactured electrode assembly can be placed in a cylindrical battery case or a prismatic battery case and then injected with an electrolyte to manufacture a battery. In a method for manufacturing a secondary battery according to another specific embodiment, the electrode assembly can be stacked and then immersed in an electrolyte, and the obtained product can be placed in a battery case and sealed to manufacture a battery.
[0102] The battery case used in this specific embodiment can use the battery case commonly used in the art. The shape is not limited according to the purpose of the battery. For example, it can be cylindrical, prismatic, pouch or coin-shaped using a can.
[0103] The secondary battery according to this specific embodiment can be used not only as a battery cell used as a power source for small devices, but can also be preferably used as a single battery cell for a medium-to-large battery module including a plurality of battery cells. Preferred examples of the medium-to-large devices include electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, power storage systems, etc., but are not limited thereto. DETAILED DESCRIPTION
[0104] Hereinafter, the embodiments of the present invention will be further described with reference to specific experimental examples. The embodiments and comparative examples included in the experimental examples are only used to illustrate the present invention and do not limit the scope of the claims of the present invention. Various changes and modifications can be made to the embodiments within the scope of the present invention and the technical concept, which is obvious to those skilled in the art, and it is natural that such variations and modifications belong to the scope of the claims.
[0105] First, the evaluation method of physical properties will be described.
[0106] 1) Solid content of electrode slurry
[0107] The weight of the electrode slurry (W1) was measured using a precision balance, and then the weight (W2) was measured again after drying in a drying oven for about 1 hour or more. The solid content was calculated according to the following formula.
[0108] Solid content (%) = W2 / W1 100
[0109] 2) Viscosity of electrode slurry
[0110] The viscosity of the electrode slurry was measured at room temperature and pressure using a Brookfield rotational viscometer in 1s. -1 The viscosity of the electrode slurry coated on the current collector is measured at a shear rate of 100 cP. The tolerance is ±100 cP.
[0111] 3) Average surface roughness Sa
[0112] The average surface roughness Sa is calculated as the average of the surface roughness values measured at any five points on the edge of the electrode active material layer in the width direction with an observation area of 20 mm in width and 20 mm in length using a surface roughness measuring tool in a confocal microscope of Keyence Corporation.
[0113] 4) Number of cracks
[0114] The number of cracks was measured using a KEYENCE confocal microscope at the edge of the electrode per unit area of 10 cm 2 The number of cracks observed in
[0115] The unit area is 10 cm 2 It is the area formed by the width a and the length b of the edge portion, and is calculated as the product of a and b. The length b is determined based on the width a of the edge portion.
[0116] 5) The maximum length of the crack
[0117] The maximum long diameter of the crack was measured using the length measurement tool in the confocal microscope produced by KEYENCE.
[0118] 6) Precipitation of lithium salts
[0119] At a temperature of 25°C, the secondary battery is charged and discharged at a C-rate of 1 / 3C. After full charge, the secondary battery is disassembled, and the precipitation of lithium salt is confirmed at the crack position of the electrode. When a large amount of lithium salt precipitation is confirmed, it is marked as "○", when a small amount of lithium salt precipitation is confirmed, it is marked as "△", and when no lithium salt precipitation is confirmed, it is marked as "#". Confirmation of a large amount of lithium salt precipitation means poor life characteristics.
[0120] {Example}
[0121] Example 1
[0122] <Negative electrode>
[0123] Artificial graphite, a conductive material, a carboxymethyl cellulose (CMC) thickener, and a styrene-butadiene rubber (SBR) binder were added to water in a weight ratio of 94.8:2.5:1.2:1.5 to prepare a first negative electrode slurry having a solid content of 51 wt % and a second negative electrode slurry having a solid content of 49 wt %, respectively.
[0124] Afterwards, on one side of the copper foil current collector with a thickness of 8μm, the first negative electrode slurry was applied to the center using a slit die head based on the width direction, and then the second negative electrode slurry was applied to the edge using a micro slit die head and then dried. Based on the total width of the applied electrode slurry, the width of the edge was 7%. The first negative electrode slurry and the second negative electrode slurry were applied to the other side of the copper foil current collector in the same way and then dried. Afterwards, the dried negative electrode was heated to 1.68g / cm 3 The negative electrode having a negative electrode active material layer formed on the current collector is manufactured by rolling under a compaction density condition of .
[0125] <Positive electrode>
[0126] As the positive electrode active material, Li[Ni 0.88 Co 0.1 Mn 0.02]O2, carbon black as a conductive material, and polyvinylidene fluoride (PVdF) as a binder were added to water at a weight ratio of 96.5:2:1.5 to prepare a positive electrode slurry. The positive electrode slurry was uniformly coated on an aluminum foil current collector with a thickness of 12 μm and vacuum dried to manufacture a positive electrode.
[0127] <Secondary Battery>
[0128] The prepared positive electrode and negative electrode are cut (notching) into specified sizes and stacked, and a separator (polyethylene, 13 μm thick) is inserted between the positive electrode and the negative electrode to form a battery cell, and then the tabs of the positive and negative electrodes are welded respectively. The welded positive electrode / separator / negative electrode assembly is placed in a soft package, and three surfaces except the electrolyte injection surface are sealed. The electrolyte is injected through the remaining surfaces except the sealing part and the remaining surfaces are sealed, and then immersed for more than 12 hours. The electrolyte is an electrolyte in which 1M LiPF6 is dissolved in a solvent of EC / EMC / DEC mixed in a volume ratio of 25:45:30, and then 1% by weight of vinylene carbonate (VC), 0.5% by weight of 1,3-propylene sultone (PRS) and 0.5% by weight of lithium bis(oxalatoborate) (LiBOB) are added based on the total weight of the electrolyte.
[0129] After that, pre-charge (pre-charging) with a current corresponding to 0.25C for 30 minutes. Degassing (degasing) after 1 hour, then aging for more than 24 hours, and forming charge and discharge (charging conditions CC-CV 0.2C 4.2V0.05C cut-off (CUT-OFF), discharge conditions CC 0.2C 2.5V cut-off). After that, standard charge and discharge (charging conditions CC-CV 0.33C 4.2V 0.05C cut-off, discharge conditions CC 0.33C 2.5V cut-off) are performed.
[0130] Example 2 to Example 3
[0131] A negative electrode, a positive electrode and a secondary battery were manufactured under the same conditions as in Example 1, except that the solid content We of the second negative electrode slurry applied on the edge portion was controlled to be the solid content described in Table 1 below.
[0132] Embodiment 4 to Embodiment 7
[0133] A negative electrode, a positive electrode and a secondary battery were manufactured under the same conditions as in Example 1, except that when the second negative electrode slurry was applied to the edge portion, the solid content ratio (We / Wc) and the edge portion described in Table 2 below were applied.
[0134] Example 8
[0135] A negative electrode, a positive electrode and a secondary battery were manufactured under the same conditions as in Example 1, except that a double-slit die coater was used on a copper foil current collector having a thickness of 8 μm, the discharge port facing the center portion was blocked with a gasket based on the width direction, the second negative electrode slurry was applied to the edge portion, and the discharge port facing the edge portion was blocked with a gasket based on the width direction, and the first negative electrode slurry was applied to the center portion.
[0136] Comparative Example 1
[0137] A negative electrode, a positive electrode and a secondary battery were manufactured under the same conditions as in Example 1, except that the solid content We of the second negative electrode slurry applied on the edge portion was controlled to be the solid content described in Table 1 below.
[0138] [Experimental Example 1]: Characteristics of negative electrode according to the solid content of electrode slurry
[0139] [Table 1]
[0140]
[0141] Below, see the results of Table 1 and Figures 5 to 7 Make an evaluation. Figures 5 to 7 In the figure, the crack is shown as the dotted area.
[0142] In Examples 1 to 3, since the range of We / Wc values defined in this specific embodiment is met, see Tables 1, Figure 5 and Figure 6 , almost no cracks were generated, or even if cracks were generated, only slight cracks were generated. In addition, in Examples 1 to 3, the average surface roughness Sa value was also as low as 5.0 μm or less, and a small amount of lithium salt precipitation was confirmed or no lithium salt precipitation was confirmed, so the life characteristics were excellent.
[0143] Among Examples 1 to 3, no cracks were generated in Examples 2 and 3, and the average surface roughness Sa value was relatively lower than that of Example 1, so they had better surface quality, and no lithium salt was precipitated, so they had relatively better life characteristics.
[0144] On the other hand, in Comparative Example 1, since the range of We / Wc value defined in this specific embodiment is not satisfied, see Tables 1 and Figure 7 , a large number of coarse cracks were generated, and the average surface roughness Sa value was too large, so the surface quality was poor, and a large amount of lithium salt precipitation was confirmed, so the life characteristics were poor.
[0145] [Experimental Example 2]: Characteristics of negative electrode according to the solid content ratio (We / Wc) of electrode slurry
[0146] [Table 2]
[0147]
[0148] Referring to the results in Table 2, in the case of Examples 1, 4, and 5 where the We / Wc value was 0.98, cracks did not occur in the wider edge portion, but large cracks occurred as the edge portion width became narrower.
[0149] In the case of Example 6 and Example 7 where the We / Wc value is 0.90 or 0.88, no cracks are generated even within the narrow width range of the edge portion. Therefore, it can be seen that compared with Example 1, Example 4, and Example 5, the difference in the drying rate of the electrode slurry applied to the edge portion and the center portion is further reduced even within the narrow width range of the edge portion, thereby further improving the surface quality and productivity of the electrode.
[0150] [Experimental Example 3]: Characteristics of negative electrode according to the coating method of electrode slurry
[0151] [Table 3]
[0152]
[0153] Referring to the results in Table 3, when the first negative electrode slurry is applied to the center portion using a slit die and then the second negative electrode slurry is applied to the edge portion using a micro slit die as shown in Example 1, it can be seen that the average surface roughness Sa value is lower than that of Example 8 using a double slit die coater, and therefore the surface quality, productivity and life characteristics are relatively excellent.
[0154] The above-described contents are merely examples of the application of the principles of the present invention, and other configurations may be included without departing from the scope of the present invention.
[0155] [Explanation of Reference Numerals]
[0156] 1: Electrode
[0157] 10: Electrode coating department
[0158] 20: Uncoated electrode
[0159] 11: Center
[0160] 12: Edge
Claims
1. An electrode for a secondary battery, comprising: current collector; as well as an electrode active material layer, wherein the electrode active material layer is located on at least one side of the current collector, And the secondary battery electrode satisfies the following relational expression 1, [Equation 1] Sa≤10.0 In the above relational expression 1, Sa is the average surface roughness value of the edge portion of the electrode active material layer based on the width direction, and the unit is μm.
2. The secondary battery electrode according to claim 1, wherein The edge portion of the electrode active material layer based on the width direction has a unit area of 10 cm 2 The number of cracks is less than 5.
3. The secondary battery electrode according to claim 1, wherein The maximum major diameter of cracks at the edge of the electrode active material layer based on the width direction is less than 100 mm.
4. A method for manufacturing an electrode for a secondary battery, comprising the following process: a) coating the electrode slurry on at least one side of the current collector; and b) drying the applied electrode slurry, And the following relationship 2 is satisfied, [Equation 2] We / Wc<1 In the above relational expression 2, based on the width direction of the applied electrode slurry, Wc is the solid content of the electrode slurry applied at the center, and We is the solid content of the electrode slurry applied at the edge.
5. The method for producing a secondary battery electrode according to claim 4, wherein: The value of We / Wc in the above relational expression 2 is greater than or equal to 0.8 and less than 1.
6. The method for producing a secondary battery electrode according to claim 4, wherein: The process a) comprises the following processes: a1) preparing a first electrode slurry having a first solid content and a second electrode slurry having a second solid content lower than the first solid content; as well as a2) On at least one side of the current collector, based on the width direction, the first electrode slurry is applied to the center portion, and the second electrode slurry is applied to the edge portion.
7. The method for producing a secondary battery electrode according to claim 6, wherein: The process a2) is carried out by the following process: On at least one side of the current collector, based on the width direction, the first electrode slurry is applied to the center portion using a slit die, and the second electrode slurry is applied to the edge portion using a micro slit die; or On at least one side of the current collector, a double slot die coater is used to apply the second electrode slurry to the edge portion and the first electrode slurry to the center portion based on the width direction.
8. The method for producing a secondary battery electrode according to claim 4, wherein: The width of the edge portion is 15% or less based on the total width of the applied electrode slurry.
9. The method for producing a secondary battery electrode according to claim 4, wherein: The electrode slurry applied to the central portion and the edge portion has the same composition.
10. The method for producing a secondary battery electrode according to claim 4, wherein: The viscosity Vc of the electrode slurry applied on the central portion is 1000-10000 cP.
11. The method for producing a secondary battery electrode according to claim 4, wherein: The viscosity Ve of the electrode slurry coated on the edge portion is 1000-6000 cP.
12. The method for producing a secondary battery electrode according to claim 4, wherein: The electrode slurry applied to the central portion and the edge portion is applied to have the same thickness.
13. A secondary battery comprising: The electrode according to any one of claims 1 to 3; a separator; and an electrolyte.
Citation Information
Patent Citations
Method for Preparing Electrode for Secondary Battery and Device for Manufacturing the Same
KR1020170100377A